2014
DOI: 10.1007/s10877-014-9609-z
|View full text |Cite
|
Sign up to set email alerts
|

The ability of the Vigileo-FloTrac system to measure cardiac output and track cardiac output changes during one-lung ventilation

Abstract: This study was aimed at comparing the cardiac output (CO) measured by the Vigileo™-FloTrac™ system with that estimated by the thermodilution pulmonary artery catheter (PAC) during one-lung ventilation (OLV) and determining the reliability of this system in tracking phenylephrine-induced CO changes during OLV. Sixteen patients scheduled for descending aorta replacement were enrolled. The study was performed 30 min after starting OLV under stable hemodynamic conditions. We recorded hemodynamic variables, CO meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Dynamic indices, such as stroke volume variation, pulse pressure variation and the pleth variability index are known to be better predictors of fluid responsiveness than static indices in mechanically ventilated patients . Among these, pleth variability index is a novel marker, allowing for continuous and automated calculation of respiratory variations in the pulse oximetry waveform amplitude .…”
mentioning
confidence: 99%
“…Dynamic indices, such as stroke volume variation, pulse pressure variation and the pleth variability index are known to be better predictors of fluid responsiveness than static indices in mechanically ventilated patients . Among these, pleth variability index is a novel marker, allowing for continuous and automated calculation of respiratory variations in the pulse oximetry waveform amplitude .…”
mentioning
confidence: 99%
“…The systematic literature search yielded 2586 records. After removing 703 duplicates and two retracted papers, we screened 1881 records and finally identified 45 studies that met the eligibility criteria [3, 15–58]. Four additional studies were identified through PubMed and Google Scholar searches and screening relevant articles' reference lists [59–62].…”
Section: Resultsmentioning
confidence: 99%
“…While minimally invasive methods relying on arterial line waveform analysis in addition to biometric and demographic data to estimate stroke volume for an individual patient are becoming more widely available [ 54 ], their effectiveness outside of goal-directed fluid therapy in terms of a true and precise reading compared to an invasive method has been questioned [ 54 ]. Additionally, the ability of these monitors to perform in the setting of one-lung ventilation has shown discordance when compared to pulmonary artery catheter values [ 55 ]. This means that any calculation of oxygen delivery will be an estimate.…”
Section: Finding the Right Balancementioning
confidence: 99%